Seismicity of Algeria from 1365 to 2013: Maximum Observed Intensity Map (MOI2014) - Ayadi, A. (2015)
Algeria is one of the most seismically active areas in the Medi- terranean basin. The available catalogs reported numerous de- structive earthquakes striking different regions, such as Algiers (1365, maximum observed intensity Io X; 1716, Io X; Ambraseys and Vogt, 1988), Oran (1790, Io X; Lopez Mari- nas and Salord, 1990), Djidjelli (1856, Io IX; Ambraseys, 1982), Orléansville (1854, Ms 6.7; Rothé, 1950), El Asnam (1980, Ms 7.3; Yielding et al., 1989), Constantine (1985, M s 5.9; Ousadou et al., 2013), Tipasa-Chenoua (1989, M s 6.0; Bounif et al., 2003), Mascara (1994, M s 6.0; Ayadi et al., 2002), and Zemmouri (2003, Mw 6.8; Harbi, Maouche, Ousadou, et al., 2007; Ayadi et al., 2008). This seismicity is related to the collision between the African and Eurasian plates and is lo- cated within the Tell Atlas of Algeria along the plate boundary zone. Two periods that are related to the installation of the Algerian seismic network are identified from the seismic cata- log of Algeria: the pre-1910 and post-1910 periods.